Progress on implantable biofuel cell: Nano carbon function alization for enzyme immobilization enhancement - Arman Amani, B.; Samira, B.; Sharifah, A.H. (Elsevier, 2016)
Biofuel cells are bio-electrochemical devices, which are suitable for the environmentally friendly generation of energy. Enzymatic biofuel cell (EBFC) operates at ambient temperature and pH. Biofuel cells utilize vegetable and animal fluids (e.g. glucose) as a biofuel to produce energy. Fundamental part of each Glucose biofuel cell (GBFC) is two bioelectrodes which their surface utilizes as an enzyme immobilized site. Glucose oxidase (GOx) or glucose dehydrogenase (GDH) were immobilized on bioanode and oxidize glucose while oxygen reduced in biocathode using immobilized laccase or bilirubin oxidase in order to generate sufficient power. Glucose biofuel cells are capable to generate sufficient power for implanted devices. The key step of manufacturing a bioelectrode is the effective enzyme immobilization on the electrode surface. Due to the thin diameter of carbon nanomaterials, which make them accessible to the enzyme active sites, they are applicable materials to establish electronic communication with redox enzymes. Carbon nanomaterials regenerate the biocatalysts either by direct electron transfer or redox mediators which serve as intermediated for the electron transfer. Nano-carbon functionalization is perfectly compatible with other chemical or biological approaches to enhance the enzyme functions in implantable biofuel cells. Efficient immobilization of enzyme using the functionalized nano-carbon materials is the key point that greatly increases the possibilities of success. Current review highlights the progress on implantable biofuel cell, with focus on the nano-carbon functionalization for enzyme immobilization enhancement in glucose/O2 biofuel cells.